DETERMINATION OF PETROLEUM HYDROCARBONS CONTENT IN SOILS FROM SUPLACU DE BARCĂU, ROMANIA - ȘEUTE, Loredana Mihaela; COSTIN, Dan Florin; ROBA, Carmen Andreea; BIZĂU-CÂRSTEA, Maria Lucia (Studia Universitatis Babeș-Bolyai Ambientum, 2020)
The level of pollution with petroleum compounds was evaluated in Suplacu de Barcău area based on the assessment of total petroleum hydrocarbons (TPH) concentrations in soil. As source of contamination, one active and another inactive petroleum extraction wells were chosen, and the concentrations were determined by fluorescence spectrometry. The results indicated alarming exceedances of the intervention thresholds, especially in the area where the activity is stopped, thus indicating long-term accumulation of pollutant and persistence in soil.